Analysis Of Data Security Systems In Business Organizations - Veronika Asri Tandirerung; Fauziah; Sul Fitriana; Putri Rahayu; Dzaky Raihan Muharram (Program Studi Teknik Komputer, 2023)
This research aims to find out the data security system at Graha Pena Makassar. Graha Pena Makassar is also called Fajar Building which was built in 2007. Graha Pena Makassar is an office building that is the main choice for investors for business development. This research was conducted by identifying potential security gaps and existing security infrastructure. This research method is observation, literature study and conducting interviews. The results showed that the data security system implemented by Graha Pena Makassar has not implemented technology or special applications for database security systems. The security system implemented is more on a physical security system.